2020
DOI: 10.1155/2020/5803639
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the NF-κB and MAPK Signaling Pathways Contributes to the Inflammatory Responses, but Not Cell Injury, in IPEC-1 Cells Challenged with Hydrogen Peroxide

Abstract: Oxidative stress can lead to intestinal cell injury as well as the induction of inflammation. It is not clear whether inflammation is an important factor leading to cell injury caused by oxidative stress. The purpose of this study was to investigate the role of inflammation in intestinal injury caused by hydrogen peroxide (H2O2). Our results revealed that H2O2 stimulation significantly decreased the viability of intestinal porcine epithelial cells (IPEC-1), increased lactate dehydrogenase (LDH) activity, and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 38 publications
1
40
0
1
Order By: Relevance
“…bioactivity and subsequently retard oxidative stress in the liver. The mitogen‐activated protein kinases (MAPKs) are mediators of intracellular signaling in response to several stressors, and inhibitors of MAPK pathways could exhibit anti‐inflammatory effects (Xiao et al., 2020). In our study, p38 MAPK activity was non‐significantly altered by PRP, an indication that PRP had no induction effect on p38 phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…bioactivity and subsequently retard oxidative stress in the liver. The mitogen‐activated protein kinases (MAPKs) are mediators of intracellular signaling in response to several stressors, and inhibitors of MAPK pathways could exhibit anti‐inflammatory effects (Xiao et al., 2020). In our study, p38 MAPK activity was non‐significantly altered by PRP, an indication that PRP had no induction effect on p38 phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that these transcription factors play critical roles in inflammatory responses in hepatic tissues (Smale & Natoli, 2014). It has been reported that NF‐κB shares a common inflammatory signaling pathway with Mitogen‐activated protein kinases (MAPKs), with their co‐activation leading to an inflammatory response via the release of pro‐inflammatory cytokines such as interleukin‐6 and tumor necrosis factor‐ α (Xiao et al., 2020). Suppression of NF‐κB and COX‐2 expressions could block the activation of downstream cytokines, and thus, afford protection against propanil‐induced hepatotoxicity (Wali, Rashid, et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Quantitative real-time PCR assay Cells were cultured as described for western blot analysis. Quantitative real-time PCR was performed as previously described to analyze gene expression [29]. In brief, total RNA was extracted using TRIzol reagent (TaKaRa Bio Inc, Japan) according to the manufacturer's instructions.…”
Section: Rna Interference and Transfection Of Ipec-j2 Cellsmentioning
confidence: 99%
“…During the inflammatory process, excessive production of reactive oxygen species (ROS) results in oxidative stress [ 6 , 7 , 8 ]. Exposure to an inflammatory component of gram-negative bacteria, lipopolysaccharide (LPS), leads to ROS-mediated activation of cell inflammatory signaling pathways such as mitogen-activated protein kinase/activator protein 1 (MAPK)/AP-1 and nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB) [ 9 , 10 , 11 ]. At the transcription level, MAPK phosphorylation, AP-1 activation, and nuclear localization of NF-κB regulate mRNA expression of key inflammatory mediators including CC chemokines such as thymus- and activation-regulated chemokine/CC chemokine ligand 17 (TARC/CCL17), macrophage-derived chemokine/CC chemokine ligand 22 (MDC/CCL22), regulated on activation normal T expressed, and secreted/CC chemokine ligand 15 (RANTES/CCL5) and interleukin-8 (IL-8) [ 12 , 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%